2020
DOI: 10.3390/medicina56040169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori Infection and Diagnostic Methods in the Middle East and North Africa Region

Abstract: Background and Objectives: Helicobacter pylori (H. pylori) infection is common worldwide and may cause gastroduodenal complications, including cancer. In this review, we examine the prevalence and distribution of various H. pylori genotypes and the risk factors for H. pylori infection, particularly in the Middle East and North Africa (MENA) region. We also introduce different global screening methods and guidelines and compare them to those currently in use in the MENA region. Materials and Methods: We searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 70 publications
(72 reference statements)
1
22
1
Order By: Relevance
“…In the Riyadh region of Saudi Arabia, Alghamdi et al [3] reported an incidence of 34.7%. Furthermore, a recent review that included published literature from Saudi Arabia reported a prevalence ranging from 27-66% in the Middle East and North Africa region [4]. The high incidence and prevalence of H. pylori infection is a public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…In the Riyadh region of Saudi Arabia, Alghamdi et al [3] reported an incidence of 34.7%. Furthermore, a recent review that included published literature from Saudi Arabia reported a prevalence ranging from 27-66% in the Middle East and North Africa region [4]. The high incidence and prevalence of H. pylori infection is a public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…We included all studies that met our eligibility criteria: (1) studies that were conducted in Arab countries and included patients who were diagnosed with H.pylori infection; (2) studies that assessed the efficacy of different H.pylori regimens; (3) studies that compare between H.pylori regimens and placebo or other regimens; (4) studies that reported data regarding eradication rate ofH.pylori , which defined as negative H.pylori stool antigen test or urea breath test 4-6 weeks after treatment; (5) studies that were experimental in design (RCT, controlled trials, or Quasi-experimental) or observational (Cohort, case-control, cross-sectional, selfcontrolled). We excluded narrative reviews, animal studies, conference abstracts, and non-English language studies.…”
Section: Eligability Criteriamentioning
confidence: 99%
“…The infection is higher in developing countries (70.1% in Africa and 69.4% in South America) than in developed countries (34.3% in Western Europe and 37.1% in North America) 1 . H. pylori infection is highly prevalent in the Middle East and North Africa (MENA) region 2 . It may cause chronic gastritis, peptic ulcer disease, atrophic gastritis, and intestinal metaplasia that predispose to gastric cancer [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the natural abundance of the isotope of interest, during the separation process it is possible to increase the isotope concentration to a desired level. Various chemical compounds based on enriched ( 13 C) have a broad field of application [ 1 ]: Applications in medical fields: in clinical studies, differential diagnosis of multiple diseases, state of illness judgment, treatment evaluation, research on organ function and development of new drugs [ 2 ], such as PET diagnosis [ 3 ], 13 C-urea breath test [ 4 ], tumor therapy (boron neutron capture therapy) research on drugs [ 5 ], etc. ; Applications in life sciences fields: in the spectrum research of the structure and function of protein species by nuclear magnetic resonance (NMR) and mass spectrometer (MS), including isotope-coded affinity tag testing method (ICATTM), stable isotope labeled amino acid cell cultivation (SILAC), absolute quantification protein analysis method (AQUATM) [ 6 ]; Applications in energy metabolism: in sports medicine, child nutrition, food nutrition, weight loss and diet for astronaut using he-isotope tracing method [ 7 ]; Applications in agricultural scientific research fields: in the research of plant physiology and biochemistry, nutrition of soil and plant, plant protection, the improvement of rice, flower, agricultural products and other crops, nitrogen cycle of grassplot [ 8 ]; Applications in the research of environmental science: monitoring of ecosystem pollution, determining of the length of food chains, ascertaining the pollutant sources in air and water and defining the distribution area of plant [ 9 , 10 ]; Applications in analysis and testing: in the testing of food [ 11 ], pesticide residue analysis [ 12 ], drug and excitant, heroin testing [ 13 ], also in the research of geology, geochemistry, paleontology and ecology [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Applications in medical fields: in clinical studies, differential diagnosis of multiple diseases, state of illness judgment, treatment evaluation, research on organ function and development of new drugs [ 2 ], such as PET diagnosis [ 3 ], 13 C-urea breath test [ 4 ], tumor therapy (boron neutron capture therapy) research on drugs [ 5 ], etc. ;…”
Section: Introductionmentioning
confidence: 99%